Detection of helicobacter pylori in gastric biopsies with urease test and histopathologic assays - Murat B. ALKANAT,; Osman ZEKİOĞLU,; Ahmet AYDIN,; Müge TUNÇYÜREK, (Turkish Journal of Gastroenterology, 2020)
-